PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT INTERNAL - Yulius, Nur Krisyulianti (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2018)
This study was conducted to examine the influence of auditor independence and competence on the quality of internal audit. The purpose of the study is to know that with the independence and competence of auditors can improve the quality of internal audit. This research was conducted at PT. Len Industries. Population in this research is auditor, finance and accounting department working in PT. Len Industries. The sampling technique was conducted by Sample Random Sampling with direct questionnaire distribution and obtained by 34 respondents. The primary data retrieval method used is questionnaire method. Analysis method used to test the hypothesis is multiple linear regression. The statistic method used to test the classical assumption first, to test the hypothesis then used t test and processed by using Statistical Product and Service Solutions (SPSS) 23.0. The results showed the influence of independence on internal audit quality by 38%. Internal auditors who have an attitude of independence will have a good impact on the quality of the audit because the higher the independence the higher the quality of audit. The influence of auditor competence on internal audit quality is 16,4% because auditor having high competence able to produce good auditquality. The result of research of influence of independence, auditor competence to internal  audit quality equal to 41,5%, it shows that the better of  independence attitude and have adequate auditor competence hence also the quality of audit resulted.